Geriatric Health in Bangladesh during COVID-19: Challenges and Recommendations. Issue 6 (2nd October 2020) - Hossain, Md Mahbub; Mazumder, Hoimonty; Tasnim, Samia; Nuzhath, Tasmiah; Sultana, Abida
ABSTRACT: The novel coronavirus disease (COVID-19) is impacting health globally, whereas older adults are highly susceptible and more likely to have adverse health outcomes. In Bangladesh, the elderly population has been increasing over the past few decades, who often live with poor socioeconomic conditions and inadequate access to healthcare services. These disparities are likely to increase amid COVID-19, which may result in high mortality and morbidity among Bangladeshi older adults. We recommend that multifaceted interventions should be adopted for strengthening social care and health systems approach to ensure wellbeing, promote preventive measures, and facilitate access to healthcare among older adults in Bangladesh. Such multipronged measures would require policy-level commitment and collaborative efforts of health and social care providers and institutions to protect health and wellbeing among this vulnerable population during the COVID-19 pandemic.